Unintentional teaching of entrepreneurial competences - Stenholm Pekka; Ramström Joachim; Franzén Riikka; Nieminen Lenita (Sage, 2022)
Research on entrepreneurship education (EE) emphasizes the role of learning environments, contexts and pedagogical choices in developing students’ entrepreneurial competences. EE has assumed that it solely carries the task of improving entrepreneurial competences. Yet, the objectives, content and methods of teaching vary, and hence non-entrepreneurship teachers’ classrooms can also provide a learning environment for entrepreneurial competences. However, whether or not this kind of unintentional teaching of entrepreneurial competences takes place has not been widely addressed. In this study, the authors investigate how business school non-entrepreneurship teachers’ teaching methods unintentionally match the known framework of entrepreneurial competences. The findings indicate that non-entrepreneurship teachers do unintentionally expose their students to entrepreneurial competences such as creativity, learning from experience and financial literacy. However, competences such as opportunity recognition, perseverance and mobilizing resources do not receive similar attention. The findings indicate that some entrepreneurial competences are not solely owned by EE, but can be embedded in non-entrepreneurship education. Accordingly, the study extends the current understanding of EE and which “niche” competences should be emphasized in it, but also demonstrates how non-entrepreneurship teachers can expose students to entrepreneurial competences while teaching in their own subject areas.